TANTANG JAWAB KREATIVITAS GURU PADA MASA PANDEMI COVID-19:: Paparan Deskriptif Penyelenggaraan Pendidikan Sekolah Dasar secara Online di Kota Palangka Raya - May Linda Sari; Retni Mulyani; Maria Angela; Sri Winda Yanti (Jurnal Teologi Pambelum, 2021)
The covid-19 pandemic has changed people's living arrangements in all areas: socially, economically, culturally, educationally, and politically. The whole world is affected, as are the Indonesians. The education sector is a sector that is quite affected by covid-19. Schools from elementary to college level must strive to adjust to survive the Pandemic while still being able to carry out their teaching well. This paper is the result of field research that seeks to discover how teachers perform their teaching obligations. The research was conducted through an online survey of elementary school teachers in Palangka Raya city, Central Kalimantan province. Elementary school teachers in Palangka Raya city are getting around this limitation by doing online teaching, although for that they have to struggle in various ways. There are three findings from this study, namely: firstly, elementary school teachers in Palangka Raya city have not been prepared to teach online because they do not get training on the use of IT in an integrated way, but only learn from friends or learn by themselves. Secondly, teachers use WhatsApp media more so that it is limited in teaching. Teachers also rely on personal data packages because most have not received assistance from the government or the school and thirdly, because of these limitations, the limited creativity of teachers makes the scope of teaching can not be implemented to the maximum.